IMPLEMENTASI KURIKULUM 2013 PADA PEMBELAJARAN BAHASA INDONESIA (Studi Kasus Kelas X di SMA Negeri 1, 2, dan 1 Bae Kudus) - Solikhah, Amaliya; J. Waluyo, Herman; Rohmadi, Muhammad (MAGISTRA, 2017)
The curriculum and learning are two inseparable things. As a program, the curriculumwill not be meaningful when not implemented in the form of learning. Along with the development of thetimes and demands of the community, then the world of Indonesian education needs to innovate, realizedwith the implementation of the curriculum 2013. Responding to the challenge made the curriculum 2013to be interesting to study. This study aims to determine and describe: (1) Indonesian language teachersâperceptions of the Curriculum 2013 Implementation; (2) the process by planning and course of learningwith the Curriculum 2013 Implementation; (3) obstacles encountered in learning with the Curriculum2013 Implementation; (4) problem solving in learning with Curriculum 2013 Implementation. Based ondata analysis, obtained some conclusions related to the teacherâs role in the implementation of Curriculum2013.Keywords: kurikulum 2013, persepsi, perencanaan, pelaksanaan